RESEARCH OF THERAPEUTIC ALTERNATIVES FOR SNAKEBITE IN AGROINDUSTRY RESIDUES OF TROPICAL FRUITS - PEREAÑEZ, Jaime A.; PATIÑO, Arley C.; CIRO, Gelmy; VARGAS, Leidy J.; VÁSQUEZ, Julieta; SALAZAR, Andrea; REY, Jessica P. (Vitae, 2009)
This paper tries to demonstrate that agroindustrial residues, such as Vitis vinifera and Citrus sinensis seeds and the Mangifera indica Kernel, have the capacity of neutralize some of the enzymatic effects induced by Bothrops asper and Porthidium nasutum venoms, in addition to the inhibitory ability of some microorganism growth of the normal flora of the serpent fangs and mouth. That is the extracts of M. indica and Vitis vinifera have a good inhibitory ability of the phospholipase A2 activity in a dose dependent manner and if they have a major neutralizing potency against the P. nasutum venom activity. Against the proteolytic effect induced by both snakes venom, V. vinifera shows the best inhibition percentages in a dependent way of the amount of extract used. Against the coagulant activity of B. asper venom, the species M. indica and V. vinifera are able to prolong the coagulation time up 31 and 13 times, respectively, to the corresponding positive control time. M. indica and V. vinifera inhibit the growth of Escherichia coli and Staphylococcus aureus. On the other hand, the etanolic extract of C. sinensis seeds does not show promising inhibition results.